Teachers defining mobile learning: Conceptualisations emerging in a development project - Jaldemark, Jimmy; Randevåg, Lena (Proceedings of the International Conference on Networked Learning, 2016)
From a historical perspective, new ICTs have rapidly been introduced in the development of higher educational settings. Such introductions have led to new ways of bridging the boundaries of time and space. In recent decades, this development has conveyed that mobile devices and social media have found their way into the teaching practices of higher education settings. However, before being implemented in the ordinary activity of teaching practices of higher education, these applications are often embraced in development projects that aim to raise the quality of higher education. One particular problem that arises in such projects is how teachers understand and conceptualise the areas of focus of the projects. One issue in projects that emphasises the introduction of mobile learning in higher education relates to how teachers define and conceptualise mobile learning. This short paper emphasises aspects of this problem. It aims to discuss and analyse emerging conceptualisations and definitions of mobile learning in higher education teaching practices. The study deals with the research question: What emerging conceptualisations and definitions of mobile learning in the teaching practices of higher education appear among teachers who participate in a development project? The project is currently in the first stage, including preliminary results from the analysis of empirical data from interviews and from observations of online teaching within six courses in a Swedish higher education institution. The interviews comprised open-ended questions. Online observations include data taken from two sources; the first source includes online dialogues of students and teachers recorded in learning management systems and various social media applications; the second source includes documents related to the teaching in the sampled courses. The initial analysis indicates that in the studied development project, different conceptualisations and definitions of mobile learning emerged. Various meanings were emphasised by the teachers of what mobile learning means and how it relates to the design of courses and to their work as teachers. Such differences might relate to interests, knowledge, beliefs and how they link mobile learning to their own processes of life-long learning. Nevertheless, the emerging definitions of mobile learning from the included teachers are preliminary in this stage of the research. To reach a more thorough understanding of the research question, the empirical data need further analysis. Moreover, the results need to be illustrated with excerpts from the interviews and the data recorded in the LMS and the additional applications applied in the studied educational settings.